A rapid and reliable method for the clonal isolation of Acanthamoeba from environmental samples - Janice Zanella; Sergio Olavo Pinto da Costa; Jucimar Zacaria; Sergio Echeverrigaray (Brazilian Archives of Biology and Technology, 2012)
Acanthamoeba are abundant in a wide range of environments, and some species are responsible for cutaneous infections, keratitis, and granulomatous amoebic encephalitis (GAE). The conventional detection and isolation of amoeba from clinical and environmental samples involves sampling and culture on non-nutrient Ágar medium. Although efficient, this system requires several transfers in order to eliminate contaminants, and is not appropriate for the isolation of individual amoeba from samples with a biodiverse community. In this study we propose an alternative method for the isolation of monocystic clones of Acanthamoeba. The propose method involves sampling, enrichment, encystment induction, and direct cysts micromanipulation and culture on Ágar plates.